(untitled) (Raparin Journal of Humanities (RJH), 2020)
After sports in the last century turned from a hobby to a professional, sports professional changed the world of sports, especially football. Some issues of legal dimensions emerged from it, including the football player professional contract, the football player’s transfer contract, and the football coach contract, And a contract to sell television broadcasting rights for competitions and matches, as this study does not deal with these contracts, but rather deals with the issue of professionalism of the player itself, and the constituent elements of it, the conditions of its stability and survival, and the procedures for its completion in order to enjoy legal protection. Professionalism is not a commodity the player buys from the sports club and the player does not acquire it by chance. Rather, he must go through some technical stages in his sports club, as well as the legal procedures covered by this study. Professionalism is represented in the player’s competence, skill, ability and sporting fame, and this can only be achieved by playing football steadily with the sports club to which the player is associated with a written contract after registering there. Through this study, the researcher tried to cover the legal aspects of the football player’s professionalism, specifically to clarify the professional, their rights and obligations regarding the use of professionalism and its exploitation, and the rights of others to professionalism. In order to achieve the goal of the study, we followed a comparative descriptive approach, and that is through a descriptive study of professionalism, identifying this phenomenon, describing it, describing its elements and its composition, then explaining how it happened, and then comparing the relevant mathematical legislative texts.